FRI0630 Can community pharmacy services be the missing link in achieving early diagnosis of psoriatic arthritis?. (12th June 2018) - Mehra, P.; Nisar, M. K.
Abstract : Background: There is an urgent need to look at New Models of Care to improve quality of care for patients whilst providing the best value for money. Community Pharmacy has been an untapped resource which can assist in achieving the goals of managing long term conditions. Psoriasis is one such example affecting 1% to 3% of the population with upto 40% of these patients at risk of developing psoriatic arthritis (PsA). There is plenty of evidence that early diagnosis of PsA remains suboptimal leading to poorer outcomes. Objectives: The objective of this proof-of-concept study was to utilise community pharmacists in collaboration with the local Rheumatology service to screen patients with psoriasis aiming to achieve earlier diagnosis of PsA. Methods: A pilot site was identified including a community pharmacy with a neighbouring GP surgery. An educational session was organised with the team to help them understand the need for the project. Logistics were finalised and a dedicated teaching was delivered covering PsA and Psoriasis Epidemiology Screening Tool (PEST) tool. PEST was chosen for its high sensitivity and specificity and positive NICE recommendation. The dispensing personnel highlighted all patients requesting prescribed standard psoriasis-treating topical applications to the pharmacists. They confirmed the history of psoriasis with the patients, ensured the absence of a formal diagnosis of arthritis and offered the PEST questionnaire. Those who scored positive were signposted to their GPs for further consultation. The data was gathered anonymously and analysed to assess the utility of the service. Results: 37 patients were identified during the 12-week proof of concept phase. 24 (65%) participants were women. Median age of the group was 48 years (range 19–73). 23/37 (62%) were white Caucasians with eight Asian and three each of Afro-Caribbean or Mixed race background. 18/37 (48%) answered yes to three or more of five-question PEST tool thereby scoring positive. Ten (27%) replies were negative and another nine (24%) declined to pariticipate. No reasons were offered for not filling in the questionnaire. Two of the positive patients have since been reviewed by GP and referred to Rheumatology for further evaluation. Conclusions: To our knowledge, this is the first study ever conducted utilising community pharmacists to employ a screening questionnaire to help early identification of possible PsA patients. This novel approach of involving community pharmacy helps explore new and proactive ways of early detection of psoriasis patients at risk of PsA and challenges the traditional model of confining the screening process to GPs in primary care. Early findings have already identified nearly half of this cohort with hitherto potentially undiagnosed PsA. This pioneering development highlights a new model of care streamlining the diagnostic pathway thereby providing better quality of care. Considering over 90% of psoriasis is managed in primary care, it would also encourage quicker assessment by a rheumatologist without burdening the already busy GP practices. Focused strategy and better utilisation of community pharmacists can be pivotal to providing better care for PsA patients in the long term. Disclosure of Interest: None declared